Rancang Bangun Monitoring Penggunaan Air dan Listrik pada Rumah Tangga Berbasis IoT - Denaldan Tabarui Landu Praing; Ilmiatul Masfufiah; Akhmad Fahruzi (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2023)
Water and electricity have become primary needs that are very often used in human life for various purposes, both in household and industrial life. Each PDAM customer's house has a water meter installed to measure water volume and water debit. However the measurement system is still manual and analog. Furthermore, the very large amount of electrical energy consumption results in a reduction in the main source of electrical energy that is widely used. Many people do not know how much electricity is consumed on a daily basis, resulting in wasted household electricity. Therefore, to overcome these problems, this research designed an IoT-based monitoring system for water and electricity use in households. IoT (Internet of Things) is a concept for continuously and remotely expanding internet connections. The water flow sensor was used to measure the water discharge. Meanwhile, the PZEM-004T sensor was applied to measure power, voltage, current, and energy in an electric current. The result of the data analysis indicated that the tool design had run as desired. The data on water consumption collected for 16 days gained 3.24 m3 at a cost of IDR 7533, while the electricity consumed 14.83 kWh at a cost of IDR 20,050.